Measuring and improving social impacts : a guide for nonprofits, companies, and impact investors - Epstein, Marc J. (Berrett-Koehler Publishers, 2014)
"The world is beset with enormous problems that desperately need solutions. And as a nonprofit, NGO, foundation, impact investor, or socially responsible company, your organization is on a mission to provide those solutions. But what exactly should you do? And how will you know whether it's working? Too many people assume that good intentions will result in meaningful actions and leave it at that. But thanks to Marc Epstein and Kristi Yuthas, social impact can now be evaluated with the same kind of precision achieved for any other organizational function. Based on years of research and analysis of field studies from around the globe, Epstein and Yuthas offer a five-step process that will help you gain clarity about the impacts that matter most to you and will provide you with methods to measure and improve those impacts. They offer a systematic approach to deciding what resources you should invest, what problem you should address, and which activities and organizations you should support. Once you've made those decisions, they provide tools, frameworks, and metrics for defining exactly what success looks like, even for goals like reducing global warming or poverty that are extremely difficult to measure. Then they show you how to use the data you've gathered to further develop and increase your social impact. Epstein and Yuthas personally interviewed leaders at over sixty different organizations for this book and include examples from nearly a hundred more. This is unquestionably the most complete, practical, and thoroughly researched guide to taking a rigorous, data-driven approach to expanding the good you do in the world"--